(3GdMcheI GdGdcJQhfjI h JWHjbGJgG aj GdhWf GdYQHj (B/s - (3GdWYGefI, eMeO eMehOs; (3GdYdhT, WGQb TQja s ((3GdbGgQI(B: s (3efThQGJ GdefXeI GdYQHjI ddJfejI GdGOGQjI(B, s, 2004)
(3GdaUd GdChd (B: (3GdMcheI GdEdCcJQhfjI (B: (3Gdeaghe hGdNUGFU (B: (3eaghe GdEOGQI GdEdcJQhfjI (B: (3eaghe GdMcheI GdEdcJQhfjI (B: (3eLGdGJ GdMcheI GdEdcJQhfjI(B-(3GdaUd GdKGfj (B: (3eYeGQjI THcGJ GdMchejI GdEdcJQhfjI (B: (3YfGUQ GdTHcGJ GdEdcJQhfjI (B: (3JQcjH GdTHcGJ GdEdcJQhfjI(B-(3GdaUd GdKGdK (B: (3GdMcheI GdEdcJQhfjI hJfbjI GdeYdheGJ (B: (3LGgRjI JbfjI GdeYdheGJ aj GSJTQGa eSJbHd hGYO ddMcheI GdEdcJQhfjI (B: (3aGQI ceHjhJQ ddecahajf(B-(3GdaUd GdQGHY (B: (3GdGJUGdGJ GdEdcJQhfjI (B: (3eJVefGJgG (B: (3eaghe GdGJUGd GdEdcJQhfjI (B: (3GdefGaY GdJj JfTOgG fXe GdGJUGdGJ GdEdcJQhfjI(B-(3GdaUd GdNGeS (B: (3efXheGJ GdGJUGd GdMOjKI (B: (3fXe GdGJUGdGJ Yf HYO (B: (3JWhQ THcI GdEfJQfJ hGSJNOGeGJgG (B: (3JWhQ THcI GdEfJQfJ (B: (3THcI GdEfJQfJ(B-(3GdaUd GdSGOS (B: (3GdefXeI GdQbejI (B: (3eaghegG hNUGFUgG (B: (3eaghe GdefXeI GdQbejI (B: (3NUGFU GdGMcheI GdEdcJQhfjI aj EWGQ GdefXeI GdQbejI (B: (3GdefXeI GdGaJQGVjI(B-(3GdaUd GdSGHY (B: (3GdMcheI GdEdcJQhfjI hGdJLGQI GdEdcJQhfjI (B: (3GdYdGbI GdefWbjI Hjf GdMcheI GdEdcJQhfjI hGdJLGQI GdEdcJQhfjI (B: (3eQGMd JfajP GdeYGedGJ GdMchejI hGdJLGQjI(B-(3GdaUd GdKGef (B: (3JWHjbGJ YQHjI aj GdMcheI GdEdcJQhfjI (B: (3GdMcheI GdEdcJQhfjI hJchjf KbGaI GdeLJeY GdYQHj (B: (3HYV ehGbY GdMcheGJ GdEdCcJQhfjI GdYQHjI (B: (3eJVefGJgG hhXGFagGs
Keywords: (3GdGOGQIs; (3GdGOGQg GdYGeg(B--(3GdHdGO GdYQHjgs; (3GdMcheGJ(B- (3GdhWf GdYQHjs; (3GdMcheGJ(B- (3JcfhdhLjGs